Numerical modelling of hygrothermal stresses in composite building facades - Zhu, Qi. (2009)
Many facade failures are probably caused, to a greater or less extent, by hygrothermal stresses due to thermal and moisture loads[29][33]. So far most studies on facade performance have considered the impacts of these two loads separately. However, heat and moisture transfer are two interrelated processes, and their synergistic impact on the facade performance may be of great importance. The author has developed a two-dimensional model for composite building facades, which can carry out transient analyses on both the simultaneous heat and moisture transfer and the induced stress distributions in the facades. The hygrothermal analysis is based on the linear Luikov's system of equations governing coupled heat and mass transfer in porous bodies. Both finite difference and finite element methods were used to numerically solve the mathematical model.